The Influence of Brand Image and Financial Technology on Customer Loyalty - Ependi, Ependi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research aims to determine the influence of Financial Technology's brand image on PT Kredit Pintar's customer loyalty. The method used in this research is a descriptive analysis method with a quantitative approach. The sample used in this research was 62 respondents using a questionnaire. The collected data was processed using multiple linear regression with SPSS 26.00. The research results show that Brand Image has a significant effect, Financial Technology has a significant effect on customer loyalty, and brand image and financial technology have a simultaneous effect on customer loyalty. This research concludes that there is a positive and significant influence on customer loyalty between brand image and financial technology. Suggestions for future researchers are that the research covers a broader scope, such as adding other variables.